Basaloid squamous cell carcinoma of the uvula: Report of a case and review of the literature. Issue 3 (May 2016) - Hara, Yuko; Ikeda, Nobuyuki; Takagi, Ritsuo; Horino, Kazuto; Iida, Akihiko; Nishiyama, Hidemasa; Hayashi, Takafumi; Cheng, Jun; Saku, Takashi
Abstract: We report a rare case of squamous cell carcinoma (SCC) with basaloid appearances arising in the uvula of a 71-year-old man. The tumor was surgically removed because it was localized only in the uvula. Histopathologically, it was mainly composed of irregular-shaped foci of basaloid SCC cells. It showed some invasive growth but was laterally continuous with foci of carcinoma in situ and epithelial dysplasia, suggesting its sequential pathogenesis from a precancerous lesion. Although the patient did not have local recurrences, he had metastatic foci in one of his right cervical lymph nodes seven months after initial surgery. We performed radical neck dissection, while he did not want to receive additional chemotherapy and radiotherapy. Fifteen months after the neck dissection, he is free from disease in terms of recurrence and metastasis of SCC. This is the first report of a primary basaloid SCC case arising in the uvula.